MoLE : a web authoring tool for building mobile learning experiences - Dal Bianco, Pedro A.; Mozzon Corporaal, Federico R.; Lliteras, Alejandra Beatriz; Grigera, Julián; Gordillo, Silvia Ethel (2020)
This paper presents a web authoring tool that allows teachers to build their own mobile learning experiences, so that their students can carry out a learning activity of the teachers authorship. In this work, a learning activity consists of a set of tasks organized through a workflow, which are given to students in relevant places (within a physical space). The workflow defines the way in which students access each of the tasks proposed in the activity. A preliminary case study and two technological implementations are presented. Although the present is a work in progress, it is based on previous works on the subject and proposes an evolution of them, incorporating technological and usability improvements both in the author's web tool and in the mobile learning application that it generates.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Workshop de Investigadores en Ciencias de la Computación (22do : 2020 : El Calafate, Argentina)
Keywords: USABILIDAD; aprendizaje móvil; flujo de trabajo